Analisis Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru di SD Negeri Rawakidang Kabupaten Tangerang - Ilmah, Siti Nurul; Latifah, Nur; Magdalena, Ina (Lembaga Yasin AlSys, 2022)
Education is a community need that is expected to create quality human beings, to realize these expectations formally education is held in schools. The purpose of this study was to determine the role of the principal's leadership in improving teacher performance at SDN Rawakidang. The method in this study used qualitative research methods with a descriptive approach, data collection techniques used observation, interviews and documentation techniques. The results of the research of the principal as the head of the school conduct training and education and invite sources from outside related to KBM and according to the 2013 curriculum, always provide direction and motivation to teachers to use active methods, always supervise when the teacher is carrying out the teaching and learning process at school. class, provide guidance to teachers and education staff, the principal asks to be present 20 minutes earlier than the students and wait for students in front of the class. conclusion The role of the principal's leadership in improving teacher performance at SDN Rawakidang is to provide a democratic, disciplined attitude, and control each class during the teaching and learning process, democratic attitudes are sought to eliminate distrust in solving problems in the classroom. as well as at school, and a disciplined attitude is sought to provide a sense of responsibility.